2021
DOI: 10.1186/s12905-021-01421-2
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian semi-parametric spatial modelling of intimate partner violence in Namibia using 2013 Demographic Health Survey Data

Abstract: Background Intimate partner violence (IPV) is an important public health problem with health and socioeconomic consequences and is endemic in Namibia. Studies assessing risk factors for IPV often use logistic and Poisson regression without geographical location information and spatial effects. We used a Bayesian spatial semi-parametric regression model to determine the risk factors for IPV in Namibia; assess the non-linear effects of age difference between partners and determine spatial effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
5
2
Order By: Relevance
“…We found that more than 10 years age difference between the partners was associated with lower odds of experiencing physical DV at the 18-year follow-up. There exist studies that found contrary results compared to our findings and argued that in patriarchal settings (such as Bangladesh), a higher age gap between the partners might reduce women’s negotiating power and result in a higher risk of violence (Ojifinni et al, 2021). This may be true, particularly at the initial period after marriage, but as shown in our study, 18 years after the birth of the index child such spousal age gap provided protection against physical violence.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that more than 10 years age difference between the partners was associated with lower odds of experiencing physical DV at the 18-year follow-up. There exist studies that found contrary results compared to our findings and argued that in patriarchal settings (such as Bangladesh), a higher age gap between the partners might reduce women’s negotiating power and result in a higher risk of violence (Ojifinni et al, 2021). This may be true, particularly at the initial period after marriage, but as shown in our study, 18 years after the birth of the index child such spousal age gap provided protection against physical violence.…”
Section: Discussioncontrasting
confidence: 99%
“…Due to the hierarchical data structure, in which individual observations are connected to the information for the municipalities, and these, in turn to the state information, we introduce random effects. To explore whether IPV follows a particular spatial pattern, as found by Ojifinni et al (2021) , we also include the municipal centroid coordinates.…”
Section: Variable Descriptionmentioning
confidence: 99%
“…Intimate partner violence (IPV) refers to all forms of behaviour within an intimate relationship that causes physical, sexual or psychological harm, including acts of physical aggression, sexual coercion, psychological abuse, and controlling behaviours [ 1 , 2 ]. It has been recognized globally as an important public health problem and a huge violation of human rights [ 3 ] which has been associated with significant morbidity and mortality as well as health and socioeconomic effects among both women and men [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…There has been growing interest in spatial analysis techniques in recent years as a tool for an in-depth understanding of public health problems including identifying IPV hotspots, spatial distribution, patterns and effects. Intimate partner violence has been shown in some studies to be spatially distributed [ 1 , 27 , 28 ], however none of the studies have used flexible structured additive regression models to estimate district spatial effects while adjusting for other covariates in studying IPV against men and women. A recent study [ 13 ] using the 2019/2020 Rwandan Demographic and Health Survey (RDHS) dataset looked at the factors associated with IPV against women and men but did not consider spatial heterogeneity of IPV.…”
Section: Introductionmentioning
confidence: 99%